Sulfated and Phosphorylated Agarose as Biomaterials for a Biomimetic Paradigm for FGF-2 Release - Aurelien Forget; V. Prasad Shastri (Biomimetics)
Cardiovascular diseases such as myocardial infarction or limb ischemia are characterized by regression of blood vessels. Local delivery of growth factors (GFs) involved in angiogenesis such as fibroblast blast growth factor-2 (FGF-2) has been shown to trigger collateral neovasculature and might lead to a therapeutic strategy. In vivo, heparin, a sulfated polysaccharide present in abundance in the extracellular matrix (ECM), has been shown to function as a local reservoir for FGF-2 by binding FGF-2 and other morphogens and it plays a role in the evolution of GF gradients. To access injectable biomaterials that can mimic such natural electrostatic interactions between soluble signals and macromolecules and mechanically tunable environments, the backbone of agarose, a thermogelling marine–algae-derived polysaccharide, was modified with sulfate, phosphate, and carboxylic moieties and the interaction and release of FGF-2 from these functionalized hydrogels was assessed by ELISA in vitro and CAM assay in ovo. Our findings show that FGF-2 remains active after release, and FGF-2 release profiles can be influenced by sulfated and phosphorylated agarose, and in turn, promote varied blood vessel formation kinetics. These modified agaroses offer a simple approach to mimicking electrostatic interactions experienced by GFs in the extracellular environment and provide a platform to probe the role of these interactions in the modulation of growth factor activity and may find utility as an injectable gel for promoting angiogenesis and as bioinks in 3D bioprinting.